2021
DOI: 10.3389/fnins.2021.720542
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and Facilitation of the Spinal Locomotor Central Pattern Generator and Reflex Circuits by Somatosensory Feedback From the Lumbar and Perineal Regions After Spinal Cord Injury

Abstract: Somatosensory feedback from peripheral receptors dynamically interacts with networks located in the spinal cord and brain to control mammalian locomotion. Although somatosensory feedback from the limbs plays a major role in regulating locomotor output, those from other regions, such as lumbar and perineal areas also shape locomotor activity. In mammals with a complete spinal cord injury, inputs from the lumbar region powerfully inhibit hindlimb locomotion, while those from the perineal region facilitate it. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 165 publications
0
17
0
Order By: Relevance
“…Although all cats recovered quadrupedal locomotion after staggered hemisections, some cats required perineal stimulation after the second hemisection ( Table 1 ), which increases spinal neuronal excitability and facilitates hindlimb locomotion in spinal mammals through an undefined mechanism (Eidelberg et al, 1980; Alluin et al, 2015; Harnie et al, 2019; Merlet et al, 2021; Audet et al, 2022). Previous studies proposed that the amount of locomotor training constitutes an important factor in locomotor recovery after partial spinal lesions (Kloos et al, 2005; Rossignol et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although all cats recovered quadrupedal locomotion after staggered hemisections, some cats required perineal stimulation after the second hemisection ( Table 1 ), which increases spinal neuronal excitability and facilitates hindlimb locomotion in spinal mammals through an undefined mechanism (Eidelberg et al, 1980; Alluin et al, 2015; Harnie et al, 2019; Merlet et al, 2021; Audet et al, 2022). Previous studies proposed that the amount of locomotor training constitutes an important factor in locomotor recovery after partial spinal lesions (Kloos et al, 2005; Rossignol et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…As described, the strength of perineal stimulation is difficult to quantify but we adjusted the pressure applied to the perineal region on a case-by-case basis (light/strong, tonic/rhythmic) to achieve the best hindlimb locomotor pattern possible (Caron et al, 2020; Audet et al, 2022). Perineal stimulation increases spinal excitability and facilitates hindlimb locomotion in spinal mammals through an undefined mechanism(Merlet et al, 2021). However, if the perineal stimulation was too strong, we observed exaggerated flexion of the hindlimbs (hip, knee and ankle) and/or improper left-right alternation, which impaired treadmill locomotion.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have also shown that scTS of the cervical area can lead to the facilitation of voluntary behaviors [28,31]. Lastly, stimulation of the sacral afferents has been shown to be an effective neuromodulator of the lower limb muscles [32,33]. We attempted to replicate this effect through scTS at the sacral-coccygeal level.…”
Section: Spinal Cord Transcutaneous Electrical Stimulationmentioning
confidence: 93%
“…Spinal cord injured animals are common models for studying neural plasticity ( Dietz and Fouad, 2014 ; Alizadeh et al, 2019 ) in the context of motor functions (respiration: Streeter et al, 2020 ; posture and locomotion: Brown and Martinez, 2019 ). Most species are capable of partial or complete recovery after SCI, demonstrating the intrinsic ability of spinal sensory-motor networks to organize functionally relevant motor commands even in the absence of part or all descending commands and neuromodulation ( Rossignol et al, 1996 ; but see also Merlet et al, 2021 ). Lumbar SCIs are more deleterious than mid-thoracic ones as reported in cats ( Rossignol et al, 2002 ) and rats ( García-Alías et al, 2006 ), probably because they may directly injure the locomotor CPG.…”
Section: Compensation After a Unilateral Lesion In Central Motor Circ...mentioning
confidence: 99%